Akad Bay’ Istishna’ di Indonesia: Indonesian - Nugroho, Mohammad Seto (Maliki Interdisciplinary Journal, 2025)
The Istishna' contract is one of the buying and selling in the Islamic religion. Since the time of the Prophet, this contract has been implemented based on the Arab culture of that time. Until the ulama' of the madzhab established the law regarding the Istishna' contract by including several conditions aimed at meeting the needs of the community by protecting their rights from cheating and deception. By using the library research method, this article aims to provide an understanding of the Istishna' contract which is also carried out by Indonesian people. Considering that Indonesia's population is predominantly Muslim, it is felt that there is a need to have regulations governing buying and selling with Istishna' contracts, so that there are no debates due to existing differences of opinion. So the Indonesian Ulema Council issued regulations regarding this contract through its fatwa No: 05/DSN-MUI/IV/2000.